Association between dietary animal-derived branched-chain amino acids and sarcopenia in older adults: a cross-sectional study based on Chinese community - Zhang, Tianfeng; Zhang, Caiyan; Du, Hongzhen; Chang, Yaping; Zhao, Kaijia; Xue, Hongmei; Liang, Mingyue; Li, Zengning (Frontiers in Nutrition, 2025)
BackgroundThe free-living dietary intake of branched-chain amino acids (BCAAs, including leucine, isoleucine, and valine) may have an impact on sarcopenia. This study aimed to compare the dietary BCAAs of animal sources related to sarcopenia in older individuals aged ≥ 55 years living in Chinese communities.MethodsWe enrolled 367 older individuals (112 males and 255 females) aged over 55 years in six communities. Sarcopenia was diagnosed based on Asian Working Group for Sarcopenia (AWGS2019). The free-living dietary intake of BCAAs was evaluated by using a 64-item food frequency questionnaire (FFQ). Multivariable logistic regression models were applied to examine the association between BCAAs and sarcopenia.ResultsThe overall prevalence of sarcopenia was 20.7% (76 in 367). The mean daily energy intake, protein, fat, and BCAAs were significantly lower in the sarcopenia older adults than in the non-sarcopenia group (p < 0.05). Logistic regression analysis revealed that increased intake of leucine (OR: 0.121, 95% CI: 0.045–0.327, p < 0.001), isoleucine (OR: 0.160; 95% CI: 0.061–0.421, p < 0.001), and valine (OR: 0.202; 95% CI: 0.076–0.534, p = 0.001) were associated with the decrease risk of sarcopenia. When stratified by food sources, animal-derived BCAAs intake was significantly associated with sarcopenia in older adults (OR: 0.819; 95% CI: 0.675–0.995, p = 0.044). However, no such association was found for plant-derived BCAAs (OR: 0.903; 95% CI: 0.742–1.098, p = 0.305).ConclusionHigh intake of dietary BCAAs was strongly associated with lower risk of sarcopenia in older adults. Animal-derived BCAAs intake may decrease the risk of sarcopenia in older adults, whereas no such effect was observed for plant-derived BCAAs.